Marine Carbonates in the Mantle Source of Oceanic Basalts: Pb Isotopic Constraints. Issue 1 (December 2018) - Castillo, P.; MacIsaac, C.; Perry, S.; Veizer, J.
Abstract For almost fifty years, geochemists have been interpreting the clues from Pb isotopic ratios concerning mantle composition and evolution separately. The Pb isotopes of ocean island basalts (OIB) indicate that their mantle source is heterogeneous, most likely due to the presence of end-components derived from recycled crust and sediment. Some OIB have unusually high206 Pb/204 Pb coming from one of the end-components with a long time-integrated high238 U/204 Pb or μ (HIMU). Most OIB and many mid-ocean ridge basalts (MORB) also have high206 Pb/204 Pb, indicating a HIMU-like source. Moreover, measured232 Th/238 U (κ) for most MORB are lower than those deduced from their208 Pb/204 Pb and206 Pb/204 Pb. Such high μ and low κ features of oceanic basalts are inconsistent with the known geochemical behavior of U, Pb and Th and temporal evolution of the mantle; these have been respectively termed the 1st and 2nd Pb paradox. Here we show that subducted marine carbonates can be a source for HIMU and a solution to the Pb paradoxes. The results are consistent with the predictions of the marine carbonate recycling hypothesis that posits the Pb isotopes of oceanic basalts indicate a common origin and/or magma generation process.